English Teachers’ Challenges in Teaching English: A Case Study at SMA Karya Ibu Palembang - Lestari, Meggi (English Education: Jurnal Tadris Bahasa Inggris, 2021)
There are many challenges faced by the teachers of English in SMA Karya Ibu Palembang. The challenges was come from the students and the facilities in the school.The aims of this study were to find out how the teachers’ challenges in teaching English, and to find out the the strategies in dealing the challenges. The participants of this study were the teachers of English of SMA Karya Ibu Palembang. The writer used qualitative research in this study. Interview was used to collect the data. Meanwhile, in order to find out the challenges that made the teachers were difficult in teaching, the data gained from interview was analyzed by using thematic analysis. The findings indicated It was found that there were five factors that made the teachers were difficult in teaching English.This study shows that the teachers were challenged by limited mastery of teaching methods, over-crowded class, inadequate facilities and resources. On the other hand, the other challenges coming from students’ side including lack of vocabulary mastery, low concentration, lack of motivation, pronunciation problem, and speaking problem.  In order to overcome those problem, there are some strategies that is used by the teachers in teaching English. First, applying various teaching methods and techniques. Second, the teacher used of available resources and facilities. The third is giving motivational feedback